2019
DOI: 10.1177/2096531119840864
|View full text |Cite
|
Sign up to set email alerts
|

English Private Tutoring in Macao: Perceptions of Senior Secondary Three Students

Abstract: Purpose: This article examines how individual, school, and social factors shape the perceptions of students in Senior Secondary Three (SS3; in some schools called Form Six [F6]) toward English private tutoring in Macao. Design/Approach/Methods: This is a comparative study of two F6 classes of an English-medium secondary school and four SS3 classes of a Chinese-medium secondary school in Macao, with a total number of 145 students. Mixed-methods approach (questionnaires and interviews) is employed in the study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Fees for these classes were lower than for external classes provided by commercial providers, such as tutoring centres. Chan found that tutees preferred to receive after-school tutoring by their schoolteachers rather than paid lessons by tutoring tutors outside (Chan 2019).…”
Section: Definition Of Terms and Focus Of The Studymentioning
confidence: 99%
“…Fees for these classes were lower than for external classes provided by commercial providers, such as tutoring centres. Chan found that tutees preferred to receive after-school tutoring by their schoolteachers rather than paid lessons by tutoring tutors outside (Chan 2019).…”
Section: Definition Of Terms and Focus Of The Studymentioning
confidence: 99%
“…If students, for instance, seek to refine already-learned study skills through shadow education, the practice adds to school. If, on the other hand, students seek extensive remedial lessons through shadow education (Bray & Kobakhidze, 2015;Chan, 2019), the practice may compensate for shortcomings in teaching. Studying what students seek from shadow education, that they do not find at school or home, can thus be a way to explore the place of shadow education in students' academic lives.…”
Section: Shadow Education Adding To or Substituting For Home And Schoolmentioning
confidence: 99%
“…Whether shadow education adds to or substitutes teachers' instruction may also depend on the instructional quality of shadow education (Chan, 2019;Zheng, Wang, Shen, & Fang, 2020). Guill, Lüdtke, and Köller (2019) elaborate on three dimensions of instructional quality of shadow education: structure, challenge, and support.…”
Section: Shadow Education Adding To or Substituting For Home And Schoolmentioning
confidence: 99%
“…The author also notes the discrepancy of the data even in vast studies on this issue. Comprehensive surveys of this problem were also carried out in Bangladesh (Nath, 2008), Taiwan (Kuan, 2011), North Korea (Chan, 2019), Hong Kong (Kwok, 2009), Germany (Guill & Lintorf, 2019), America (Buchmann et al, 2010) and Japan (Entrich, 2017).…”
Section: Introductionmentioning
confidence: 99%